What Makes Management Research Interesting, And Why Does It Matter? - Bartunek, Jean M.; Rynes, Sara L.; Ireland, R. Duane (Academy of Management Journal, 2006)
This article discusses management research and what makes it interesting. In a well-known paper, “That’s Interesting!” Murray Davis argued that what most makes scholarly work interesting is that it disconfirms some (but not all) of the assumptions held by its audience. Davis’ arguments about what constitutes interesting research are summarized, including something that engages readers’ attention, something that stands out for readers “in contrast to the web of routinely taken-for-granted propositions which make up the structure of their everyday life.” Some perspectives from a Brazilian scholarly journal, “Revisita de Administracao de Empresas,” are also presented.